INTEGRASI SWOT KUANTITATIF DAN KUALITATIF UNTUK MENYUSUN PERENCANAAN STRATEGIS BIDANG PENDIDIKAN - Adam Prasetyo Wibowo; Suharno Suharno; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2021)
This research aims at finding out (1) quadrant position of each study program in the departement Ex Schools of Language and Arts Education (PBS) FKIP UNS using SWOT analysis method. (2) strategic planning study program of Javanese Language Eduction in the Departement of Ex Schools of Language and Arts Education (PBS) FKIP UNS development efforts study program by using the SWOT method.The results of research show that : (1) quadrant position of Education of Visual Arts Study Program and Language and Literature of Indonesia Studies Program are located in quadrant I (strength-opportunity). Javanese Education Studies Program and English Education Study Program are located in quadrant II (strength-treath). (2) Strategic planning that can be applied to the Javanese Education Study Program in the effort of developing study program using SWOT matrix that is (a) capacity building of human resources (b) making the student achievement program (mawapres) become the flagship program for the students (c) conduct a disciplined and responsible implementation of the curriculum (d) reproduce international journal publications for lecturers of Javanese Education Studies Program (e) increase the regular infrastructure maintenance (f) analyzing the budget needs to make the draft budget (g) Apply work based learning in student learning (h) Develop clear SOP organizational management study program (i) Improve communication between universities and the employment (j) improve the performance of multimedia and information teams in the study program (k) improve cooperation relationships with institutions partner (l) cooperate with the government in the regions to distribute the graduates of the study program (m) improve the quality and quantity of research programs and community service